2013
DOI: 10.3390/jdb1020112
|View full text |Cite
|
Sign up to set email alerts
|

Epicardium Formation as a Sensor in Toxicology

Abstract: Zebrafish (Danio rerio) are an excellent vertebrate model for studying heart development, regeneration and cardiotoxicity. Zebrafish embryos exposed during the temporal window of epicardium development to the aryl hydrocarbon receptor (AHR) agonist 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exhibit severe heart malformations. TCDD exposure prevents both proepicardial organ (PE) and epicardium development. Exposure later in development, after the epicardium has formed, does not produce cardiac toxicity. It is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The finding that nicotine treatment alone recapitulated untreated controls indicates that the impact of e-cigarette and tobacco cigarette on heart development is the consequence of other components. Many chemicals, including known ingredients in tobacco cigarettes such as polycyclic aromatic hydrocarbons can cause gross morphological defects [ 43 46 ]. Reports have also shown significant toxicity from e-cigarette treatment [ 12 , 13 , 47 ] with some reports showing the cause to be the presence of cinnamaldehyde and 2-methoxycinamaldehyde in e-cigarette flavorings [ 48 , 49 ], the presence of formaldehyde in e-cigarette vapor[ 50 ], and tin particles in cartomizer fluid [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that nicotine treatment alone recapitulated untreated controls indicates that the impact of e-cigarette and tobacco cigarette on heart development is the consequence of other components. Many chemicals, including known ingredients in tobacco cigarettes such as polycyclic aromatic hydrocarbons can cause gross morphological defects [ 43 46 ]. Reports have also shown significant toxicity from e-cigarette treatment [ 12 , 13 , 47 ] with some reports showing the cause to be the presence of cinnamaldehyde and 2-methoxycinamaldehyde in e-cigarette flavorings [ 48 , 49 ], the presence of formaldehyde in e-cigarette vapor[ 50 ], and tin particles in cartomizer fluid [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCF21 promotes the expression of AHR heterodimer partner ARNT AHR and cooperates with these factors to upregulate some inflammatory downstream disease-related genes, including IL1A, MMP1, and CYP1A1. TCF21 binds to AHR, ARNT, and downstream target gene loci, and the binding sites of AHR-ARNT and TCF21 are colocated throughout the genome of HCASMC open chromatin region [84]. These co-localization regions were found to be enriched with GWAS signals associated with cardiac metabolism and chronic inflammatory disease phenotypes.…”
Section: The Role Of Tcf21 In Inflammatory Mechanismsmentioning
confidence: 99%
“…Conversely, excessive activation of AHR can mediate inflammatory responses, leading to atherosclerosis in mice (Wu et al, 2011). It has been found that 2,3,7,8-tetrachlorodibenzop-dioxin (TCDD) can inhibit epicardial formation during cardiac development by activating the AHR pathway, resulting in developmental malformations, volume reduction, decreased cardiomyocyte numbers, blood regurgitation, and conduction block in the heart (Antkiewicz et al, 2005;Hofsteen et al, 2013). TCDD-like compounds and polycyclic aromatic hydrocarbons (PAHs) are the two main types of environmental pollutants known to activate the AHR signaling pathway.…”
Section: Aromatic Hydrocarbon Receptor Pathwaymentioning
confidence: 99%